Genomic imprinting: a possible mechanism for the parental origin effect in Huntington's chorea. Issue 12 (December 1988) - Reik, W
Abstract : Huntington's disease (HD) is an autosomal dominant condition with almost complete penetrance. The age of onset of the symptoms, however, is variable and depends on the parental origin of the gene. A high proportion of early onset cases inherit the HD gene from their father, whereas a considerable proportion of late onset cases inherit the gene from their mother. Modification of the HD gene by maternally inherited extrachromosomal factors has been invoked to account for the parental origin effect. Recent experimental evidence suggests genomic imprinting as an alternative mechanism, by which the gene itself becomes modified in a different way depending on whether it is passed through the maternal or the paternal germline. This modification may involve methylation of DNA and could result in earlier or higher level expression of the gene when it is transmitted by the father.